Relevansi Pembiayaan Haji pada Pegadaian Syariah Lhokseumawe dengan Fatwa MUI No: 92 Tahun 2014 - Iswandi, Iswandi (Syarah: Jurnal Hukum Islam dan Ekonomi, 2022)
The presence of arrum haji products in Islamic pawnshops KCP Lhokseumawe makes people obsessed with borrowing money at Islamic pawnshops. However, this has also led to a sense of doubt and curiosity and even anxiety to customers about arrum Hajj products. This is because indirectly financing Hajj through arrum Hajj products seem the same as financing Hajj through Hajj bailout funds. In addition, the Qur'an also states that Hajj is only required for those who are able to carry it out, not vice versa. Of course this becomes a dilemma that has implications for customer anxiety and unrest. To get a definite answer related to the legal status of Hajj financing through arrum Hajj products, this study was studied using qualitative methods. The nature of this study is normative empirical. The results of this study is that the product arrum Hajj at pegadaian syariah KCP Lhokseumawe different from the financing of Hajj through bailout Hajj. In addition, the financing of Hajj through arrum Hajj products in terms of mechanisms and operations is relevant to the provisions of the Mui DSN Fatwa number: 92/DSN-MUI/IV/2014 on financing accompanied by Rahn, the law may register Hajj through arrum Hajj products. However, it is better to perform Hajj do not use borrowed funds or debt.